Analisis Kapabilitas Proses pada Domain Manajement SPBE di Diskominfo Kota Tasikmalaya Berdasarkan PERMENPAN-RB No. 59 Tahun 2020 - Diyan Anjani (UNIVED Press, 2023)
Abstract— The current administration of government processes focuses a lot on the use of technology and information, especially in providing electronic services to improve services so that they are fast, efficient, and comfortable, in which case the issuance of PERPRES Regulation Number 95/20118 concerning SPBE. In 2021 the City of Tasikmalaya gets an SPBE index value of 2.68 with the smallest value in the SPBE Management domain, the purpose of this study is to evaluate the SPBE Management domain, with 2 aspects and 11 indicators based on PERMENPAN guidelines Number 59 of 2020. Assessment is carried out using the Qualitative method by conducting surveys and interviews with employees within the scope of the Tasikmalaya City Communication and Information Service and attached with supporting evidence. The results of this study show that the Tasikmalaya City government in 2022 in the SPBE Management domain gets a domain index value of 2.28, indicators that are classified as low in this study are recommendations for the Tasikmalaya City government in the future.